PENGARUH SOSIAL DAN BUDAYA TERHADAP PEMAHAMAN MASYARAKAT TENTANG PENDIDIKAN ANAK DI DESA KARANG ASEM JENU - Agus Fathoni Prasetyo; Dwi Aminatus Sa'adah (Institut Agama Islam Nahdlatul Ulama Tuban, 2026)
Children’s education constitutes a fundamental pillar in the development of high-quality human capital. This study examines the influence of social and cultural factors on community perceptions of children’s education in Karangasem Village, Jenu District. Employing a quantitative survey design, data were collected from 40 respondents, including adolescents, parents, and educators, through structured questionnaires covering demographic characteristics, family support, cultural values, and educational perceptions. The findings reveal that social factors—particularly family support and community interactions—alongside cultural dimensions such as local traditions and patriarchal norms, significantly shape community understandings of the value of education, especially for girls. Despite an increasing awareness of the importance of formal education, persistent challenges remain, including economic limitations, inadequate educational infrastructure, and deeply rooted traditional beliefs that constrain access to higher education.This study argues that improving educational outcomes in rural contexts requires a multidimensional and context-sensitive approach. It highlights the necessity of collaborative engagement among governmental institutions, civil society organizations, and local communities to address structural and cultural barriers. Strategic interventions—such as expanding educational access, strengthening community awareness, and enhancing parental capacity—are essential to fostering inclusive and sustainable educational development. Ultimately, this study contributes to the sociology of education by demonstrating how social and cultural structures interact in shaping educational aspirations and opportunities in rural communities, while offering practical insights for policy and community-based interventions.